A Missing Link in Radial Ion Transport: Ion Transporters in the Endodermis - Bao, Zhulatai; Bai, Juan; Cui, Hongchang; Gong, Chunmei (Frontiers in Plant Science, 2019)
In higher plants, roots have important functions, such as the acquisition of water and ions, as well as transportation into the aerial parts of the plant via the xylem vessels. Radial ion transport in the root is strongly regulated in the endodermis, which is characterized by the presence of the Casparian strip and suberin lamellae. Although tremendous progress has been made with regard to the ion transporters and endodermal cells, little is known about the relationship between the ion transporters in the endodermis and ion homeostasis in aboveground tissues. This review summarizes the current knowledge about the location of the ion transporters (or channels) in the endodermis. We mainly discuss the effects of mutants related to the Casparian strip and/or suberin formation on the role of endodermal ion transporters in ion homeostasis. We also wish to emphasize the critical role of endodermal ion transporters in the regulation of radial ion transport in the root.